Heterogeneous parameter uncertainty and the timing of investment during crisis - Shawn Ni; Ronald A. Ratti (Economics: The Open-Access, Open-Assessment E-Journal, 2009)
We present a model in which investors observe the same macroeconomic data but have varying levels of information about the parameters that determine the distribution of the expected returns on investment. During a crisis that increases macroeconomic uncertainty and reduces asset prices, the threshold required return that triggers investment is lower for an informed investor than for an uninformed investor. Simulation of the model suggests that when macroeconomic uncertainty is high investment may increase, is mostly by informed investors, and as time goes on is progressively more by investors who were initially relatively uninformed about model parameters. For over 10,000 instances of firm-level FDI data for Korea from 1996 to 2001, regression results are consistent with the hypothesis that disproportionably more FDI is made by more informed investors during a period of high macroeconomic uncertainty.
Keywords: D8; E2; F4; 330; Parameter uncertainty; investor information; option value; Bayesian updating; FDI; Investition; Direktinvestition; Entscheidung bei Unsicherheit; Konjunktur; Realoption; Theorie; Südkorea